Persepsi F&B Product Terhadap Pengawasan Mutu Makanan dan Minuman di Hotel Alam KulKul Boutique Resort Kuta-Bali - Margaretta Andini Nugroho (Journal of Tourism and Creativity, 2019)
Abstract This study aimed at finding food and beverages quality control procedures in purchasing, receiving, and stores section and find out the F & B's perception of the quality control of food and beverages products by purchasing, receiving, and stores section. The result of the research shows that the quality control procedures are carried out by purchasing and receiving is quite appropriate with the operational standards specified, as for the food control procedures by the store the result was good. Solution based is the purchasing must do more quality control on groceries, the receiving must do increase knowledge of the quality standards of food, and the store must do repair of storage space to keep the temperature and humidity.Keywords : Perception, F & B Product, Food and Beverages Quality Control